PRECEDENTES E DECISÕES (POTENCIALMENTE) VINCULANTES: OBRIGATORIEDADE RACIONAL E OBRIGATORIEDADE FORMAL NA LEI PROCESSUAL - Cunha, Gabriel Sardenberg (2020)
Aiming for more rationality in the jurisdictional activity and aligned with the recent discussions in Legal Theory and Philosophy, the 2015 Code of Civil Procedure dogmatically structured a model of judicial precedents with binding authority formalized in